2013
DOI: 10.1128/cvi.00609-12
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Frequency of a CD14+CD16+Monocyte Subset with High Toll-Like Receptor 4 Expression in Cord Blood Compared to Adult Blood Contributes to Lipopolysaccharide Hyporesponsiveness in Newborns

Abstract: The human innate immune response to pathogens is not fully effective and mature until well into childhood, as exemplified by various responses to Toll-like receptor (TLR) agonists in newborns compared to adults. To better understand the mechanistic basis for this age-related difference in innate immunity, we compared tumor necrosis factor alpha (TNF-␣) production by monocytes from cord blood (CB) and adult blood (AB) in response to LAM (lipoarabinomannan from Mycobacterium tuberculosis, a TLR2 ligand) and LPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 63 publications
1
20
1
Order By: Relevance
“…Following isolation of mononuclear cells, we found no differences in leukocyte percentages and no differences in DC subsets between adult and cord blood. We also found that classical and inflammatory monocyte subsets are the same between cord and adult mononuclear cells, an observation previously reported in the literature (42,45,46) but in conflict with another report that suggested that decreased populations of monocytes could be responsible for observed hyporesponsiveness to LPS seen in neonates (41). Importantly, within our cohort, we found that monocytes isolated from either adult or neonate stimulated with CNA or TLR ligands mirrored the IFN response observed in the PBMC/CBMC system.…”
Section: Discussioncontrasting
confidence: 78%
“…Following isolation of mononuclear cells, we found no differences in leukocyte percentages and no differences in DC subsets between adult and cord blood. We also found that classical and inflammatory monocyte subsets are the same between cord and adult mononuclear cells, an observation previously reported in the literature (42,45,46) but in conflict with another report that suggested that decreased populations of monocytes could be responsible for observed hyporesponsiveness to LPS seen in neonates (41). Importantly, within our cohort, we found that monocytes isolated from either adult or neonate stimulated with CNA or TLR ligands mirrored the IFN response observed in the PBMC/CBMC system.…”
Section: Discussioncontrasting
confidence: 78%
“…UCB contained a lower number of CD14 + CD16 + monocytes, which are known as activated monocytes, than APB. Concomitant with our findings, reduction of inflammatory CD14 + CD16 + monocytes in UCB and its implications for weak immune responses of newborns to infections has been demonstrated [21]. Here, we observed that PGE2 level in the UCB plasma has inverse correlation with the frequencies of CD14 + CD16 + cells.…”
supporting
confidence: 79%
“…UCB and APB exhibit difference in the ratio of CD14 + CD16 + monocytes to CD14 + CD16 -monocytes. UCB displays significantly reduced frequency in CD14 + CD16 + monocytes [21]. However, it is yet to be elucidated whether the lower proportions of CD14 + CD16 + monocytes in UCB have a correlation This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction.…”
Section: Introductionmentioning
confidence: 98%
“…In one previous study, monocyte subset frequencies as defined by CD14 and CD16 markers (classical monocytes-CD14++ CD16- and inflammatory monocytes-CD14+CD16+) were found to be similar in AB and CB [30] whereas another study reports inflammatory monocytes (CD14+ CD16+) to be lower in CB [31]. Both these papers do not mention patrolling monocytes.…”
Section: Discussionmentioning
confidence: 99%